Replacement of Standard Apple Cultivars with Coloured Strains for High Profitability in Shimla District of Himachal Pradesh, India: A Success Story - Kaith, N. S.; Bandana; Kumari, Neelam; Thakur, Ashok K.; Banshtu, Tanuja (International Journal of Economic Plants, 2017)
The Delicious cultivars of apple, grown traditionally in Shimla district of Himachal Pradesh (India), possess some inherent problems like low spur formation, less fruit set, poor coloration at lower elevation and valley area and delayed maturity at higher elevation. These problems lead to declined productivity and returns. The introduction of spur cultivars overcome these problems as these are precocious, spur bearing with better colour development. KVK Shimla provided the planting material of spur cultivars for establishing new orchards as well as converting the Delicious cultivars into spur by top working. KVK also imparted trainings on various top working techniques and training and pruning of spur cultivars. The diligent efforts of KVK Shimla resulted in shifting of >25% area (9500 ha) to spur type and coloured strains. An average increase of 10 t ha-1 in yield was observed in spur cultivars compared to Delicious cultivars.